Aluminum Oxide Support Layer for Vertical Growth of Single Walled Carbon Nanotube using Alcohol Catalytic CVD Technique - Asyadi Azam, Mohd; Fujiwara, Akihiko; Shimoda, Tatsuya (2011)
We report our research work on different type of Al oxide support layer in order to produce VA-SWCNTs. The electron beam (EB) deposition was mainly used to deposit high purity Al and Al2O3 thin film (20 nm). For the as-deposited Al metal layer, several oxidation treatments were elucidated to confirm the different in physical and chemical structures to act as catalyst support material. The post deposition oxidation treatments are natural oxidation, thermal oxidation, UV ozone, and plasma ashing oxidation. Characterization and analytical studies will be carried out by XPS, XRD, AFM, and SEM in order to understand what type of Al oxide support layer is suitable to support Co catalyst for VA-SWCNTs growth. This important research work is a reliable and good approach to deeply understand the step-by-step mechanism before implementing the device or application oriented studies.